PENGARUH UKURAN PARTIKEL DAN RASIO BAHAN TERHADAP PELARUT AIR PADA DISTILASI MINYAK ATSIRI TEMULAWAK - Eni Budiyati; Angga Fredo Nugroho; Ristiana Fauziati (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Javanese turmeric (Curcuma xanthorrhiza) essential oil is one of the curcuminoids sources that are widely used in the food and health industries. Temulawak oil extraction usually uses ethanol as a solvent which is relatively less safe for health. This study aimed to evaluate the effect of particle size and the ratio of materials to water solvents in the distillation process of Javanese turmeric essential oil. The experiment was conducted at the Chemical Engineering Research Laboratory, Muhammadiyah University, Surakarta. The treatments tested were the powder size (20, 40, 60, dan 140 mesh), the ratio of material to water solvent (w/v) consisted of 100:800, 150:750, 200:700, and a distillation time of 3 hours at a constant temperature of 100oC with an interval of distillation duration of 0.5; 1; 1.5; 2; 2.5; and 3 hours. The parameters observed were the essential oil quality: organoleptic, refractive index, pH, mass or volume of the oil produced, and curcuminoid compounds using the GC-MS method. The maximum yield of Javanese turmeric essential oil (18.01g) was obtained at a particle size of 140 mesh with a distillation duration of 1.5–2 hours, and the ratio of raw material to solvent 100:800 (g.ml-1). Based on the GCMS analysis, the highest components in the Javanese turmeric essential oil were α-curcumin (42.17%) and α-cedrene (11.14%). The results indicated that the distillation process of Javanese turmeric oil using water as a solvent can be used as an alternative to substitute ethanol as a solvent.